DETERMINATION OF FLAVONOIDS OF WILLOW TRIANDRA (SALIX TRIANDRA L.), GROWING IN THE NORTH CAUCASUS - E. G. Sannikova; O. I. Popova; O. O. Frolova; A. U. Airapetova (Фармация и фармакология (Пятигорск), 2016)
Plants of willow genus are rich in various flavonoids. In 60-e years of the XX century the works of V. A. Kompantsev showed that leaves of willow triandra, growing in the North Caucasus, contain up to 5% of rutin. The method, which required long sample preparation (extraction of the raw material with TLC, chromatographic layer extraction with methanol, removal of the solvent, dissolution in ethanol, optical density measurements) was used. Currently available and simple methods for the determination of rutin in plant material are described. Given that leaves of Salix triandra contain significant amounts of rutin and can be a potential raw material for the creation of medicines on their basis, it is essential to determine the amount of flavonoids in the leaves of Salix triandra and its branches.The purpose of this study is determination of the amount of flavonoids in the willow triandra, growing in the North Caucasus, depending on the place and time of collection.Methods. TLC and the method of differential spectrophotometry were used to study chemical reactions. Results. The presence of flavonoids in various vegetative plant organs was established using qualitative reactions (cyanidin test; boric-citric reaction; the reaction with solution of lead acetate and solution of ammonia). Rutin and quercetin flavonoids in the presence of standard samples were identified using TLC. the method of differential spectrophotometry, based on the reaction of flavonoids with aluminum chloride was used for the quantitative determination of the amount of flavonoids. It is shown that the greatest quantity of flavonoids amount accumulated in the leaves (up to 3.76%), its value in branches is slightly smaller (up to 3.26%). The branches without leaves have almost 10 times less flavonoids. It was established experimentally that the accumulation of flavonoids in raw material of Salix triandra is dependent on the place and time of raw materials gathering.Conclusion. The results confirmed the previously obtained information about the fact that Salix triandra mainly contains rutin. The method of differential spectrophotometry allows determining the amount of flavonoids with a relative error not exceeding 2.5%.